Choosing the service support model after a merger: Case Are Ltd. - Junni, Salla (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2015)
The meaning of information technology (IT) and information systems have increased during the last few years. This is mainly because business is nowadays seen more and more as a service business and IT is one of the key elements to support those business services. Since the meaning of IT services has increased also the meaning of IT service support should be a factor paid more attention to. Especially after a merger and acquisition (M&A) it is more important than ever to consider service support. The purpose of this study is to discover the best practices for choosing a suitable service support model. The research question is How to choose a service support organization model for the ERP service desk function after a merger? A qualitative method is selected as a research method. This thesis includes two parts: a literature review and a case study. Theoretical part compiles an integrated model of previous research on the topic. It consists a collection of academic articles, publications and reports. The empirical part focuses on the issues in the case organization. That part tries to answer the question: what would be the most suitable service support model for the case organization? The empirical part is conducted by interviewing the employees of the case organization. This study finds that even though there are many ways of selecting a service support model it is difficult to define an unambiguous guidelines. However, there are few main objectives that should be taken into account regardless the case. Especially by using ITIL processes it is possible to implement a comprehensive service support and raise overall awareness of the existing service support models. The main functions that need to be taken into account are nature, industry and size of the organization. Also the business strategy, goals and resources need to be considered. These are the same factors that are noticed in the case study as well. The suggestions for the case organization are presented based on the interviews and the literature review.